Pembuatan Bolu dengan Substitusi Tepung Pisang Goroho - Datunsolang, Irwan (Gorontalo Agriculture Technology Journal, 2018)
This research is to determine the manufacture of bolu substitution basic flour banana goroho. this study using the design of randomized complete (RAL) with three treatment three times replay, a1 formulated flour banana goroho 150gr and wheat flour 50gr, a2 formulated flour banana goroho 100gr and wheat flour 100gr, a3 formulated flour banana goroho50 grams and wheat flour 150gr. parameters analyzed is water content, ash content, level of carbohydrate and test organoleptic (color, taste, aroma and texture). the results showed that the treatment a2 with the formulation of flour banana goroho 100gr and wheat flour 100gr is the best treatment which can produce bolu preferred by panelists terms, taste, aroma and texture. scent that 4,00, sense that 4,23, and texture that 4,37. and have ash content meet the standards of quality National Indonesia and has a level of carbohydrate 18,37%., water content 27,71% and ash content 1,30% Â Keywords : sponge, wheat flour, flour banana goroho